Kinematics and shear-induced alignment in confined granular flows of elongated particles. (1st July 2022) - Pol, Antonio; Artoni, Riccardo; Richard, Patrick; Nunes da Conceição, Paulo Ricardo; Gabrieli, Fabio
Abstract: The kinematics and the shear-induced alignment of elongated particles in confined, heterogeneous flow conditions are investigated experimentally. Experiments are conducted in an annular shear cell with a rotating bottom wall and a top wall permitting confinement of the flow. Flow kinematics and particle orientation statistics are computed by particle tracking using optical imaging. Translational velocity profiles show an exponential decay, and surprisingly, only the slip velocity at the bottom is influenced by the particle shape. Rotations are highly frustrated by particle shape, more elongated particles showing, on average, a lower angular velocity. In addition, a clear shear-rate dependency of the proneness of a particle to rotate is observed, with a stronger inhibition in low shear zones. The average orientation of the particles does not correspond to the main flow direction, they are slightly tilted downwards. The corresponding angle decreases with the particles' elongation. Orientational order was observed to increase with particles' elongation, and surprisingly was not affected by the applied confinement. A weak but systematic decrease of the orientational order was observed in regions of higher shear rate. At the particle-scale, angular velocity fluctuations show a strong correlation with local particle orientation, particles being strongly misaligned with the preferential particles' orientation rotating faster. This correlation becomes stronger for more elongated particles, while is almost unaffected by the applied confinement.